Natural Radioactive Contamination in Shampoo and Dishwashing Samples Used in Iraq by NaI(Tl) Detector - Abid Abojassim*, Ali; Hamad Al-Gazaly, Hussain; Sabah Obide, Eman (Asian Journal of Chemistry, 2016)
In Iraqi markets, there are no sufficient comprehensive study to identify the natural radioactivity in detergents samples such as shampoo and dishwashing. The aim of the present research is to measure the natural radioactivity in different types of shampoo and dishwashing samples are available in Iraq markets. Also, it is to calculate the radiological hazard indices such as radium equivalent activities and external hazard indices for samples. Measurements were made, using gamma spectrometer for gamma emission such as 238U, 232Th and 40K. Results show that the average values of specific activity in shampoo and dishwashing liquid samples for 238U, 232Th and 40K were (3.50 ± 0.60) Bq/kg, (1.77 ± 0.22) Bq/kg and (119.60 ± 7.27) Bq/kg, respectively. The radium equivalent activity and external hazard index were calculated from the measured natural radioactivity. The average values of the radium equivalent activity and external hazard index in samples under study were (172.22 ± 10.30) Bq/kg and (0.46 ± 0.02), respectively. The present study show that the radium equivalent activity and external hazard index due to natural radioactivity were found within below the action level recommended which are (370 Bq/kg and 1) according to Organization for Economic Cooperation and Development and International Commission on Radiological Protection. It is concluded that the samples of the products under study are well below the limits recommended by recognized authorities.